Penerapan Metode Analytic Hierarchy Process (AHP) pada Proses Mitigasi Bencana : Narrative Literatur Review - Nailis Sa’adah (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Decision making with the application of the Analytic Hierarchy Process (AHP) Method has been widely applied in various fields. One of them is in the field of disaster mitigation. This study aims to determine the types of disaster mitigation that apply the AHP Method in determining decisions. The research method uses the Narrative Review Method to describe and analyze various research literature on disaster mitigation using the AHP Method. The research method begins with a literature search with a limitation of 2019-2024 and the literature is only in the form of articles that have been published. 11 related articles were found that were successfully summarized. The results of the study stated that there are several types of research articles related to disaster mitigation that have implemented the AHP Method in their decision support systems, such as in research on flood-prone zoning, landslide-prone zoning, priority alternatives for flood control efforts, landslide risk factors, analyzing tsunami disaster risks, air evacuation routes and others.